The Temporal Contribution of the Gbx2 Lineage to Cerebellar Neurons - Hagan, Nellwyn; Guarente, Juliana; Ellisor, Debra; Zervas, Mark (Frontiers in Neuroanatomy, 2017)
The cerebellum (Cb) is an exquisite structure that controls elaborate motor behaviors and is essential for sensory-motor learning. During development, the Cb is derived from rhombomere 1 (r1). Within this embryonic compartment, precursors in r1 are patterned by signaling cues originating from the isthmus organizer (IsO) and subsequently undergo complex morphogenic movements to establish their final position in the mature Cb. The transcription factor Gbx2 is expressed in the developing Cb and is intimately involved in organizing and patterning the Cb. Nevertheless, how precursors expressing Gbx2 at specific embryonic time points contribute to distinct cell types in the adult Cb is unresolved. In this study, we used Genetic Inducible Fate Mapping (GIFM) to mark Gbx2-expressing precursors with fine temporal resolution and to subsequently track this lineage through embryogenesis. We then determined the terminal neuronal fate of the Gbx2 lineage in the adult Cb. Our analysis demonstrates that the Gbx2 lineage contributes to the Cb with marking over the course of five stages: Embryonic day 7.5 (E7.5) through E11.5. The Gbx2 lineage gives rise to Purkinje cells, granule neurons, and deep cerebellar neurons across these marking stages. Notably, the contribution of the Gbx2 lineage shifts as development proceeds with each marking stage producing a distinct profile of mature neurons in the adult Cb. These findings demonstrate the relationship between the temporal expression of Gbx2 and the terminal cell fate of neurons in the Cb. Based on these results, Gbx2 is critical to Cb development, not only for its well-defined role in positioning and maintaining the IsO, but also for guiding the development of Cb precursors and determining the identity of Cb neurons.